2004
DOI: 10.1103/physrevlett.93.095504
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Freezing and Melting of Gallium Encapsulated in Carbon Nanotubes

Abstract: The freezing and melting behavior of gallium (Ga) encapsulated in carbon nanotubes was investigated through in situ observation in a transmission electron microscope. It is shown that Ga remains liquid up to -80 degrees C when encapsulated in carbon nanotubes. Results of detailed electron diffraction analysis show that the encapsulated Ga can crystallize in either beta phase or gamma phase rather than the common alpha phase upon freezing. Both beta-Ga and gamma-Ga melt at around -20 degrees C. While this is ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
86
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 25 publications
4
86
0
Order By: Relevance
“…Using values obtained in liquid phase epitaxy for our two doping levels gives Si polycrystalline. Ga drops on planar surfaces [8] and Ga encapsulated in carbon nanotubes [7] were found to crystallize in the same two metastable Ga phases that can even coexist in the same particle.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Using values obtained in liquid phase epitaxy for our two doping levels gives Si polycrystalline. Ga drops on planar surfaces [8] and Ga encapsulated in carbon nanotubes [7] were found to crystallize in the same two metastable Ga phases that can even coexist in the same particle.…”
mentioning
confidence: 94%
“…The possibility of significant supercooling in small droplets has been investigated extensively following the pioneering work of Turnbull [1]. It has been shown that small particles can melt and freeze at temperatures different from the bulk [2][3][4], undergo significantly higher supercooling [4], crystallize along different pathways [5], and in structures different from the bulk [6][7][8][9][10][11]. The extent of achievable supercooling can presumably vary with droplet size, purity [12], interactions with supports, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[23] In our experiments, a magnification of 4000 and a second condenser lens aperture were typically used. The electron current density, projected onto the transmission electron microscopy full screen, was varied in the range of ca.…”
mentioning
confidence: 99%
“…Nanothermometer can operate in conditions with high temperature changes where conventional measurement systems, such as thermometer and thermocouple, almost fail. Carbon nanothermometer was rst proposed by Gao et al [30] who accidently discovered that CNTs lled with gallium can be used as a device to measure temperature between 50 C to 500 C. Liu et al [31] examined the freezing and melting characteristics of gallium encapsulated in CNTs through insitu observation in a TEM. Their study showed that the state of gallium encapsulated in CNTs is liquid up to 80 C. The precision of measuring through gallium-lled CNT nanothermometer is dependent on its identi cation and calibration in a TEM which can impose limitations on its applicability.…”
Section: Introductionmentioning
confidence: 99%